Experimental Ethics
X, 304 p.
Keywords: Moral philosophy is no longer being pursued from arm-chairs. Instead, ethical questions are dissected in the experimental lab. This volume enables its readers to immerse themselves into Experimental Ethics' history, its current topics and future perspectives, its methodology, and the criticism it is subject to.